![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
(x+3)3:3-1=-10
(x+3)3:3=1-10
(x+3)3:3=-9
(x+3)3=(-9).3
(x+3)3=-27
(x+3)3=33
x+3=3
x=3-3
x=0
Ta có : ( x + 3 ) 3 : 3 - 1 = -10
<=> ( x + 3 ) 3 : 3 = ( -10 ) + 1
<=> ( x + 3 ) 3 : 3 = ( -9)
<=> ( x + 3 )3 =(- 9 ) . 3
<=> ( x + 3 )3 = (-27 )
<=> x + 3 = (-3)
<=> x = ( - 3) - 3
<=> x = -6
Vậy x = -6
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{x-2}{4}=\frac{5+x}{3}\)
\(\Leftrightarrow3\left(x-2\right)=4\left(5+x\right)\)
\(\Leftrightarrow3x-6=20+4x\)
\(\Leftrightarrow3x-4x=20+6\)
\(\Leftrightarrow-x=26\)
\(\Leftrightarrow x=-26\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{7}{x}=\frac{y}{27}=-\frac{42}{54}\)
\(\Leftrightarrow\frac{7}{x}=\frac{y}{27}=-\frac{7}{9}\)
Có \(\frac{7}{x}=-\frac{7}{9}\)
\(\Leftrightarrow x=-9\)
Lại có \(\frac{y}{27}=-\frac{7}{9}\)
\(\Leftrightarrow x=-21\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(72^{45}-72^{44}=72^{44}.\left(72-1\right)=72^{44}.71\)
\(72^{44}-72^{43}=72^{43}.\left(72-1\right)=72^{43}.71\)
Vì \(72^{44}>72^{43}\Rightarrow72^{45}-72^{44}>72^{44}-72^{43}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
S = 1 + 2 + 23 + ... + 29
=> 2S = 2 + 22 + 23 + ... + 210
=> 2S - S = S = 2 + 22 + 23 + ... + 210 - (1 + 2 + 23 + ... + 29)
=> S = 2 + 22 + 23 + ... + 210 - 1 - 2 - 23 - ... - 29
=> S = 210 - 1
lại có 5.28 = (4 + 1).28 = 4.28 + 28 = 22 . 28 + 28 = 210 + 28 mà S = 210 - 1
=> 5.28 > S
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 4.x - 15 = -75 - x
=> 4x + x = -75 + 15
=> 5x = -60
=> x = -60/5 = -12
b) 72 - 3.x = 5.x + 8
=> -3x - 5x = 8 - 72
=> -8x = -64
=> x = -64/-8 = 8
5.23.|\(x\)| - 2511 = 72
5.8.|\(x\)| = 72 + 2511
40.|\(x\)| = 2583
|\(x\)| = 2583 : 40
|\(x\)| = 64,575
\(\left[{}\begin{matrix}x=-64,575\\x=64,575\end{matrix}\right.\)